Cloning and Characterization of Yak DHODH Gene and Its Functional Studies in a Bisphenol S-Induced Ferroptosis Model of Fetal Fibroblasts - Hongmei Xu; Yueyue Li; Qiao Li; Zifeng Ma; Shi Yin; Honghong He; Yan Xiong; Xianrong Xiong; Daoliang Lan; Jian Li; Wei Fu (Animals, 2023)
Dihydroorotate dehydrogenase (DHODH) is a rate-limiting enzyme of de novo biosynthesis of pyrimidine. Although the involvement of DHODH in resisting ferroptosis has been successively reported in recent years, which greatly advanced the understanding of the mechanism of programmed cell death (PCD), the genetic sequence of the yak DHODH gene and its roles in ferroptosis are still unknown. For this purpose, we firstly cloned the coding region sequence of DHODH (1188 bp) from yak liver and conducted a characterization analysis of its predictive protein that consists of 395 amino acids. We found that the coding region of the yak DHODH gene presented high conservation among species. Second, the expression profile of the DHODH gene in various yak tissues was investigated using RT-qPCR. The results demonstrated that DHODH was widely expressed in different yak tissues, with particularly high levels in the spleen, heart, and liver. Third, to investigate the involvement of DHODH in regulating ferroptosis in cells, yak skin fibroblasts (YSFs) were isolated from fetuses. And then, bisphenol S (BPS) was used to induce the in vitro ferroptosis model of YSFs. We observed that BPS decreased the cell viability (CCK8) and membrane potential (JC-1) of YSFs in a dose-dependent manner and induced oxidative stress by elevating reactive oxygen species (ROS). Simultaneously, it was evident that BPS effectively augmented the indicators associated with ferroptosis (MDA and BODIPY staining) and reduced GSH levels. Importantly, the co-administration of Ferrostatin-1 (Fer), a potent inhibitor of ferroptosis, significantly alleviated the aforementioned markers, thereby confirming the successful induction of ferroptosis in YSFs by BPS. Finally, overexpression plasmids and siRNAs of the yak DHODH gene were designed and transfected respectively into BPS-cultured YSFs to modulate DHODH expression. The findings revealed that DHODH overexpression alleviated the occurrence of BPS-induced ferroptosis, while interference of DHODH intensified the ferroptosis process in YSFs. In summary, we successfully cloned the coding region of the yak DHODH gene, demonstrating its remarkable conservation across species. Moreover, using BPS-induced ferroptosis in YSFs as the model, the study confirmed the role of the DHODH gene in resisting ferroptosis in yaks. These results offer valuable theoretical foundations for future investigations into the functionality of the yak DHODH gene and the underlying mechanisms of ferroptosis in this species.